Covid-19 transmission in fitness centers in Norway - a randomized trial - Lise M. Helsingen; Magnus Løberg; Erle Refsum; Dagrun Kyte Gjøstein; Paulina Wieszczy; Ørjan Olsvik; Frederik E. Juul; Ishita Barua; Henriette C. Jodal; Magnhild Herfindal; Yuichi Mori; Solveig Jore; et al. (BMC, 2021)
Abstract Background Closed fitness centers during the Covid-19 pandemic may negatively impact health and wellbeing. We assessed whether training at fitness centers increases the risk of SARS-CoV-2 virus infection. Methods In a two-group parallel randomized controlled trial, fitness center members aged 18 to 64 without Covid-19-relevant comorbidities, were randomized to access to training at a fitness center or no-access. Fitness centers applied physical distancing (1 m for floor exercise, 2 m for high-intensity classes) and enhanced hand and surface hygiene. Primary outcomes were SARS-CoV-2 RNA status by polymerase chain reaction (PCR) after 14 days, hospital admission after 21 days. The secondary endpoint was SARS-CoV-2 antibody status after 1 month. Results 3764 individuals were randomized; 1896 to the training arm and 1868 to the no-training arm. In the training arm, 81.8% trained at least once, and 38.5% trained ≥six times. Of 3016 individuals who returned the SARS-CoV-2 RNA tests (80.5%), there was one positive test in the training arm, and none in the no-training arm (risk difference 0.053%; 95% CI − 0.050 to 0.156%; p = 0.32). Eleven individuals in the training arm (0.8% of tested) and 27 in the no-training arm (2.4% of tested) tested positive for SARS-CoV-2 antibodies (risk difference − 0.87%; 95%CI − 1.52% to − 0.23%; p = 0.001). No outpatient visits or hospital admissions due to Covid-19 occurred in either arm. Conclusion Provided good hygiene and physical distancing measures and low population prevalence of SARS-CoV-2 infection, there was no increased infection risk of SARS-CoV-2 in fitness centers in Oslo, Norway for individuals without Covid-19-relevant comorbidities. Trial registration The trial was prospectively registered in ClinicalTrials.gov on May 13, 2020. Due to administrative issues it was first posted on the register website on May 29, 2020: NCT04406909 .